The effect of a uterine manipulator on the recurrence and mortality of endometrial cancer: a multi-centric study by the Italian Society of Gynecological Endoscopy - Uccella, Stefano; Bonzini, Matteo; Malzoni, Mario; Fanfani, Francesco; Palomba, Stefano; Aletti, Giovanni; Corrado, Giacomo; Ceccaroni, Marcello; Seracchioli, Renato; Shakir, Fevzi; Ferrero, Annamaria; Berretta, Roberto; et al. (American journal of obstetrics and gynecology, 2017)
Although widely adopted, the use of a uterine manipulator during laparoscopic treatment of endometrial cancer represents a debated issue, and some authors hypothesize that it potentially may cause an increased risk of relapse, particularly at specific sites. Our aim was to evaluate the risk and site of disease recurrence, overall survival, and disease-specific survival in women who had laparoscopic surgery with and without the use of a uterine manipulator. Data were reviewed from consecutive patients who had laparoscopic surgery for endometrial cancer staging in 7 Italian centers. Subjects were stratified according to whether a uterine manipulator was used during surgery; if so, the type of manipulator was identified. Multivariable analysis to correct for possible confounders and propensity score that matched the minimize selection bias were utilized. The primary outcome was the risk of disease recurrence. Secondary outcomes were disease-specific and overall survival and the site of recurrence, according to the use or no use of the uterine manipulator and to the different types of manipulators used. We included 951 patients: 579 patients in the manipulator group and 372 patients in the no manipulator group. After a median follow-up period of 46 months (range,12–163 months), the rate of recurrence was 13.5% and 11.6% in the manipulator and no manipulator groups, respectively (P=.37). Positive lymph nodes and myometrial invasion of >50% were associated independently with the risk of recurrence after adjustment for possible confounders. The use of a uterine manipulator did not affect the risk of recurrence, both at univariate (odds ratio, 1.18; 95% confidence interval, 0.80–1.77) and multivariable analysis (odds ratio, 1.00; 95% confidence interval, 0.60–1.70). Disease-free, disease-specific, and overall survivals were similar between groups. Propensity-matched analysis confirmed these findings. The site of recurrence was comparable between groups. In addition, the type of uterine manipulator and the presence or not of a balloon at the tip of the device were not associated significantly with the risk of recurrence. The use of a uterine manipulator during laparoscopic surgery does not affect the risk of recurrence and has no impact on disease-specific or overall survival and on the site of recurrence in women affected by endometrial cancer.